Case Report: Primary Indolent Epstein-Barr Virus-Positive T-Cell Lymphoproliferative Disease Involving the Central Nervous System - Wang, Kun; Li, Jinjian; Zhou, Xuehui; Lv, Junhui; Wang, Yirong; Li, Xinwei (Frontiers in Surgery, 2022)
Background T-cell lymphoproliferative disease (T-LPD), characterized by primary Epstein–Barr virus (EBV) infection and clonal proliferation of T cells, occurs both in systemic and non-lymphatic organs. However, isolated indolent EBV-positive T-LPD involving the central nervous system has not been reported. Case Presentation A 48-year-old male who complained of headache, blurred vision, and weakness of the left lower limb for 1 month was hospitalized in our department. Neither neurological deficit nor palpable lymphadenopathy had been found. Bone marrow and laboratory tests had shown no abnormality as well. Enhanced MRI demonstrated enhanced cotton-like lesions up to 20 mm in diameter located in the right frontal, temporal, parietal and left parietal, occipital lobes with perifocal edema. Neuronavigation-assisted mini-craniotomy was performed to achieve total excision of the right temporal superficial lesion and identify the diagnosis. Pathological and EBV analysis described the lesion as indolent EBV-positive T-cell lymphoproliferative disease of the central nervous system (CNS). Then, a therapeutic regimen including whole-brain irradiation, chemotherapy, prednisolone, and aciclovir was given. Serial radiological imaging showed no signal of recurrence at 5 months' follow-up. Conclusion Primary indolent T-LPD in the central nervous system is quite rare, and it needs to be distinguished from aggressive cerebral T-cell lymphoma, metastatic tumors, and other CNS lesions.